2003
DOI: 10.4049/jimmunol.170.12.6040
|View full text |Cite
|
Sign up to set email alerts
|

Immunologically Induced, Complement-Dependent Up-Regulation of the Prion Protein in the Mouse Spleen: Follicular Dendritic Cells Versus Capsule and Trabeculae

Abstract: The expression of the prion protein (PrP) in the follicular dendritic cell network of germinal centers in the spleen is critical for the splenic propagation of the causative agent of prion diseases. However, a physiological role of the prion protein in the periphery remains elusive. To investigate the role and function of PrP expression in the lymphoid system we treated naive mice i.v. with preformed immune complexes or vesicular stomatitis virus. Immunohistochemistry and Western blot analysis of the spleen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…4). From 10 days onward, PrP c labeling was also seen in the spleen capsule and trabeculae, as has been reported previously for adult mice (32). No labeling was seen in control spleen sections from age-matched PrP-deficient mice or in control spleen sections from PrP-expressing mice where the PrP-specific antibody had been replaced with normal rabbit serum (not shown).…”
Section: Resultssupporting
confidence: 84%
“…4). From 10 days onward, PrP c labeling was also seen in the spleen capsule and trabeculae, as has been reported previously for adult mice (32). No labeling was seen in control spleen sections from age-matched PrP-deficient mice or in control spleen sections from PrP-expressing mice where the PrP-specific antibody had been replaced with normal rabbit serum (not shown).…”
Section: Resultssupporting
confidence: 84%
“…Cashman and colleagues (1990) have reported that in peripheral lymphoid cells polyclonal antibodies directed against PrP C can inhibit lectin-induced activation of human T cells, and this was recently confirmed in a similar system using monoclonal antibodies ). PrP C expression in mouse splenocytes has been widely documented, and despite the fact that these splenocytes possess much less PrP C surface immunoreactivity than human lymphocytes (Holada and Vostal 2000;Liu et al 2001;Parizek et al 2001;Lötscher et al 2003), splenocytes derived from PrP 0/ 0 129/Ola mice show decreased proliferation following lectin treatment (Mabbott et al 1997). The low level of expression we observe in spleen cells is consistent with previous reports (Mabbott et al 1997;Holada and Vostal 2000;Liu et al 2001;Parizek et al 2001;Lötscher et al 2003).…”
Section: Discussionsupporting
confidence: 92%
“…The aging-related factors responsible for the downregulation of PrP C expression by FDCs are uncertain. Data suggest that PrP C expression by FDCs is upregulated by immune complex trapping (29). In the absence of complement component C1q, the upregulation of PrP C could not be provoked.…”
Section: Discussionmentioning
confidence: 89%